Analysis of Product Quality, Brand Image, and Price on Purchase Decisions in Richeese Factory Medan Marelan Consumers - Sonia, Preity; Siregar, Nurafrina (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
The rapid development of the times has had a great influence on the culinary industry, especially in the fast food culinary industry. One of the fast food culinary industries is Richeese Factory. The researcher chose Richeese Factory as the object of research because based on the Top Brand Index of the last 5 years, Richeese Factory always occupies the last position in the retail category with a fast food restaurant sub-category. This study aims to determine the effect of product quality, brand image, and price on buying decisions on consumers of Richeese Factory Medan Marelan. The research was quantitative research. The population was consumers who buy at Richeese Factory in Medan Marelan. The sampling technique is a simple random sampling technique. The number of samples used was 100. The data sources used are primary and secondary data with data collection techniques using questionnaires. The analysis method used is multiple linear regression analysis with the SPSS (Statistic Product and Service Solution) application tool. The results of this study show that the variables of product quality, brand image, and price have a positive and significant effect on purchasing decisions on Richeese Factory Medan Marelan consumers.